Integration of the Kansas Department of Agriculture Division of Animal Health Zoonotic Diseases into the EpiTrax Online Reporting System - Grace, Jami (My University, 2014)
The Kansas Department of Agriculture (KDA) was the United States first state department of agriculture. The agency is devoted to the total support of agriculture in Kansas. The department works for the entire Kansas agriculture sector, including farmers, ranchers, food establishments and agribusinesses. Within this role, the Kansas Department of Agriculture also fulfills its responsibility of regulating business functions in accordance with state law. KDA is organized in a variety of divisions and programs that provide different services; there are a total of 13 different departments or services. The EpiTrax system is currently utilized through the Kansas Department of Health and Environment (KDHE) for maintenance, surveillance and tracking of reportable human health diseases in the state of Kansas. The Department of Agriculture Division of Animal Health wants to partner with KDHE to offer a similar system for the tracking and surveillance of reportable zoonotic and animal-only diseases. The Epitrax system employs Disease Investigation Guidelines, Disease Fact Sheets and Individual Case Reporting Forms as a way to manage and maintain information in a useful manner. This report presents the details of an internship completed at the Department of Agriculture Division of Animal Health (KDA-DAH). Projects worked on during this internship included designing these “Disease Investigation Guidelines”, creation of the disease information fact sheets and development and implementation of disease case report templates. These templates are the core structure behind being able to online report and track disease information to facilitate disease control through the KDA-DAH. I also participated in general rounds held by the Kansas Department of Health and Environment (KDHE). The Department of Agriculture Division of Animal Health hosted a Rip Stop exercise during the second week in October. This was a functional exercise designed to portray a “real-life” simulation of a Foot and Mouth Disease (FMD) outbreak originating in Alabama and ending up at the Kansas State Veterinary Health Center. This involved all levels of local, state and federal agencies; it was designed to monitor the response and management of an FMD outbreak. All projects were completed within the internship timeframe and provided valuable experience and awareness of the intertwined working relationships at the state level of public and animal health.
Keywords: Kansas department of agriculture; Epitrax; Disease case report templates; Public Health (0573)